CN113433389A - Method and device for testing ionic conductivity of diaphragm - Google Patents
Method and device for testing ionic conductivity of diaphragm Download PDFInfo
- Publication number
- CN113433389A CN113433389A CN202110703139.2A CN202110703139A CN113433389A CN 113433389 A CN113433389 A CN 113433389A CN 202110703139 A CN202110703139 A CN 202110703139A CN 113433389 A CN113433389 A CN 113433389A
- Authority
- CN
- China
- Prior art keywords
- diaphragm
- testing
- stainless steel
- resistance value
- test
- Prior art date
- Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
- Pending
Links
- 238000012360 testing method Methods 0.000 title claims abstract description 85
- 238000000034 method Methods 0.000 title claims abstract description 33
- 229910001220 stainless steel Inorganic materials 0.000 claims abstract description 33
- 239000010935 stainless steel Substances 0.000 claims abstract description 33
- 239000012528 membrane Substances 0.000 claims abstract description 18
- XKRFYHLGVUSROY-UHFFFAOYSA-N Argon Chemical compound [Ar] XKRFYHLGVUSROY-UHFFFAOYSA-N 0.000 claims description 28
- 239000010410 layer Substances 0.000 claims description 24
- 229910052786 argon Inorganic materials 0.000 claims description 14
- -1 lithium hexafluorophosphate Chemical compound 0.000 claims description 10
- 239000002356 single layer Substances 0.000 claims description 10
- 239000004809 Teflon Substances 0.000 claims description 7
- 229920006362 Teflon® Polymers 0.000 claims description 7
- 238000010586 diagram Methods 0.000 claims description 7
- KMTRUDSVKNLOMY-UHFFFAOYSA-N Ethylene carbonate Chemical compound O=C1OCCO1 KMTRUDSVKNLOMY-UHFFFAOYSA-N 0.000 claims description 6
- 239000003792 electrolyte Substances 0.000 claims description 6
- JBTWLSYIZRCDFO-UHFFFAOYSA-N ethyl methyl carbonate Chemical compound CCOC(=O)OC JBTWLSYIZRCDFO-UHFFFAOYSA-N 0.000 claims description 6
- IEJIGPNLZYLLBP-UHFFFAOYSA-N dimethyl carbonate Chemical compound COC(=O)OC IEJIGPNLZYLLBP-UHFFFAOYSA-N 0.000 claims description 5
- 238000010998 test method Methods 0.000 claims description 4
- 239000004745 nonwoven fabric Substances 0.000 claims description 3
- 239000004698 Polyethylene Substances 0.000 claims description 2
- 239000004743 Polypropylene Substances 0.000 claims description 2
- 239000004760 aramid Substances 0.000 claims description 2
- 229920003235 aromatic polyamide Polymers 0.000 claims description 2
- 150000002500 ions Chemical class 0.000 abstract description 19
- HBBGRARXTFLTSG-UHFFFAOYSA-N Lithium ion Chemical compound [Li+] HBBGRARXTFLTSG-UHFFFAOYSA-N 0.000 abstract description 13
- 229910001416 lithium ion Inorganic materials 0.000 abstract description 13
- 238000002360 preparation method Methods 0.000 abstract description 5
- 239000010405 anode material Substances 0.000 abstract description 4
- 239000010406 cathode material Substances 0.000 abstract description 4
- 230000035515 penetration Effects 0.000 abstract description 3
- 239000000463 material Substances 0.000 description 8
- BASFCYQUMIYNBI-UHFFFAOYSA-N platinum Chemical compound [Pt] BASFCYQUMIYNBI-UHFFFAOYSA-N 0.000 description 6
- 238000010079 rubber tapping Methods 0.000 description 3
- WHXSMMKQMYFTQS-UHFFFAOYSA-N Lithium Chemical compound [Li] WHXSMMKQMYFTQS-UHFFFAOYSA-N 0.000 description 2
- 230000005611 electricity Effects 0.000 description 2
- 238000011156 evaluation Methods 0.000 description 2
- 229910052744 lithium Inorganic materials 0.000 description 2
- 229910052697 platinum Inorganic materials 0.000 description 2
- 229920006231 aramid fiber Polymers 0.000 description 1
- 230000009286 beneficial effect Effects 0.000 description 1
- 239000002131 composite material Substances 0.000 description 1
- 230000007547 defect Effects 0.000 description 1
- 238000011161 development Methods 0.000 description 1
- 238000004146 energy storage Methods 0.000 description 1
- 238000010438 heat treatment Methods 0.000 description 1
- 238000009434 installation Methods 0.000 description 1
- 239000003014 ion exchange membrane Substances 0.000 description 1
- 239000007788 liquid Substances 0.000 description 1
- 239000011148 porous material Substances 0.000 description 1
- 238000012545 processing Methods 0.000 description 1
- 238000007789 sealing Methods 0.000 description 1
- 238000006467 substitution reaction Methods 0.000 description 1
Images
Classifications
-
- G—PHYSICS
- G01—MEASURING; TESTING
- G01R—MEASURING ELECTRIC VARIABLES; MEASURING MAGNETIC VARIABLES
- G01R27/00—Arrangements for measuring resistance, reactance, impedance, or electric characteristics derived therefrom
- G01R27/02—Measuring real or complex resistance, reactance, impedance, or other two-pole characteristics derived therefrom, e.g. time constant
-
- G—PHYSICS
- G01—MEASURING; TESTING
- G01R—MEASURING ELECTRIC VARIABLES; MEASURING MAGNETIC VARIABLES
- G01R1/00—Details of instruments or arrangements of the types included in groups G01R5/00 - G01R13/00 and G01R31/00
- G01R1/02—General constructional details
- G01R1/04—Housings; Supporting members; Arrangements of terminals
- G01R1/0408—Test fixtures or contact fields; Connectors or connecting adaptors; Test clips; Test sockets
-
- G—PHYSICS
- G01—MEASURING; TESTING
- G01R—MEASURING ELECTRIC VARIABLES; MEASURING MAGNETIC VARIABLES
- G01R1/00—Details of instruments or arrangements of the types included in groups G01R5/00 - G01R13/00 and G01R31/00
- G01R1/02—General constructional details
- G01R1/04—Housings; Supporting members; Arrangements of terminals
- G01R1/0408—Test fixtures or contact fields; Connectors or connecting adaptors; Test clips; Test sockets
- G01R1/0425—Test clips, e.g. for IC's
Landscapes
- Physics & Mathematics (AREA)
- General Physics & Mathematics (AREA)
- Secondary Cells (AREA)
Abstract
The invention provides a method and a device for testing ionic conductivity of a diaphragm, wherein the method comprises the following steps: and assembling the batteries with different membrane layers, respectively carrying out alternating current impedance test on each battery, carrying out linear fitting on resistance value data obtained by testing, and calculating the ion passing rate of the membrane. In the invention, the conductivity in the thickness direction of the diaphragm is tested by adopting the testing device of the diaphragm ion conductivity to evaluate the diaphragm ion passing rate, the precision is higher, the preparation is simpler, and the method can directly simulate the impedance generated by the penetration of lithium ions through the diaphragm. Meanwhile, the method does not need to use anode and cathode materials, but adopts the stainless steel wafer as the symmetrical electrode, so that the cost is saved, and the influence of other interference factors on the test is reduced.
Description
Technical Field
The invention belongs to the technical field of lithium ion battery testing, relates to lithium ion battery diaphragm testing, and particularly relates to a method and a device for testing diaphragm ionic conductivity.
Background
With the gradual application of lithium ion batteries in the fields of automobile power, energy storage, unmanned aerial vehicles and the like, the lithium ion batteries also have a wide attention of consumers, and although the lithium ion batteries have unique advantages compared with the traditional battery lithium ion batteries, with the update iteration of electronic products, people begin to put forward more requirements on the performance of the lithium ion batteries, which leads to the reason that new lithium ion battery materials are developed rapidly in recent years. With the rapid development of lithium ion battery related materials, the testing method of new lithium ion battery materials tends to be refined and normalized, so it is necessary and significant to develop a new testing method of materials.
CN206618804U discloses a device for testing battery diaphragm conductivity, the device includes conductivity cell casing, conductivity cell lid, diaphragm anchor clamps and conductivity meter, conductivity cell casing is one end opening cylinder barrel-shaped, the bottom internal surface has first circular conductivity electrode piece, the surface has the first electrode external tapping that is connected with first circular conductivity electrode piece electricity, two electrode external tapping are used for connecting the conductivity meter, conductivity cell lid detachable insert be fixed in conductivity cell casing open end, the internal surface has the second circular conductivity electrode piece, the surface has the second electrode external tapping that is connected with the second circular conductivity electrode piece electricity, vacuum valve port and notes liquid valve port have been seted up respectively to conductivity cell casing lateral wall, diaphragm anchor clamps are the formula ring structure of interlockable, diaphragm anchor clamps external diameter and conductivity cell casing internal diameter adapt to, parallel and the center is coaxial with two conductivity electrode pieces. The device of this application, simple structure, the processing ease can accurate convenient conductivity and the resistance that surveys the diaphragm.
CN111579871A discloses a battery diaphragm ionic conductivity testing device and a testing method, including: a shell provided with an installation hole, a clamping structure detachably arranged in the shell, wherein the clamping structure comprises a first clamping part and a second clamping part, the first clamping part and the second clamping part are respectively provided with a first through hole and a second through hole, a diaphragm placing gap is formed between the first clamping part and the second clamping part, a first electrode is arranged on one side of the shell in a manner that the first electrode can move left and right, and is connected with the outer side wall of the clamping structure, a groove formed with the first through hole, a second electrode arranged at the other side of the shell in a manner of moving left and right, the second electrode connected with the outer side wall of the clamping structure, the battery diaphragm electric conductivity tester comprises a groove formed by the battery diaphragm and a second through hole, a heating structure arranged on a first electrode and a second electrode, and a temperature measuring structure arranged in the groove formed by the second electrode and the second through hole.
CN209542503U discloses a film conductivity testing arrangement belongs to ion exchange membrane conductivity test technical field, and the device includes the piece base member, and piece base member middle part is equipped with fixed anchor clamps down, and the both ends of fixed anchor clamps down are equipped with platinum net electrode, and fixed anchor clamps are equipped with fixed anchor clamps in the fixed anchor clamps top down, and piece base member one side is equipped with the through-hole, is equipped with the platinum wire in the through-hole, and fixed anchor clamps are connected to the one end of platinum wire. The utility model discloses a can lock the relative position of platinum mesh electrode and the film that awaits measuring, make to measure more accurately, slotted hole and the ventilative pinhole on the mounting fixture are convenient for vapor and are pierce through, have reduced measuring error.
Based on the requirements of high energy density and quick charging of the current lithium battery, two functional requirements of thinning and high ion passing rate are provided for the lithium battery diaphragm. At present, pore channels inside a commonly-used PE, PP or a composite diaphragm of the PE and the PP are often complex, and challenge is provided for the testing accuracy of the diaphragm rate sub-throughput rate, so that a testing method of an electrochemical testing device with higher accuracy and simpler preparation and an evaluation method of the diaphragm ion throughput rate need to be provided, the testing period of developing a functional diaphragm is accelerated, the testing consumption is reduced, the interference of other interference factors on the diaphragm ion throughput rate is reduced, and the testing accuracy is improved.
Disclosure of Invention
Aiming at the defects in the prior art, the invention aims to provide a method and a device for testing the ionic conductivity of a diaphragm. Meanwhile, the method does not need to use anode and cathode materials, but adopts the stainless steel wafer as the symmetrical electrode, so that the cost is saved, and the influence of other interference factors on the test is reduced.
In order to achieve the purpose, the invention adopts the following technical scheme:
in a first aspect, the present invention provides a method for testing ionic conductivity of a separator, the method comprising: and assembling the batteries with different membrane layers, respectively carrying out alternating current impedance test on each battery, carrying out linear fitting on resistance value data obtained by testing, and calculating the ion passing rate of the membrane.
In the invention, the conductivity in the thickness direction of the diaphragm is tested by adopting the testing device of the diaphragm ion conductivity to evaluate the diaphragm ion passing rate, the precision is higher, the preparation is simpler, and the method can directly simulate the impedance generated by the penetration of lithium ions through the diaphragm. Meanwhile, the method does not need to use anode and cathode materials, but adopts the stainless steel wafer as the symmetrical electrode, so that the cost is saved, and the influence of other interference factors on the test is reduced.
As a preferred technical scheme of the invention, the test method comprises the following specific steps:
assembling batteries with different membrane layers, respectively carrying out alternating current impedance test on each battery, carrying out alternating current impedance test on the batteries with different membrane layers, and recording resistance value data of the batteries;
(II) drawing a Bode diagram and a Nyquist diagram according to the resistance value data of the battery, and performing linear fitting on the resistance value and the number of the corresponding diaphragm layers according to the y ═ ax + b, thereby obtaining the resistance value in the thickness direction of the single-layer diaphragm, wherein: y is a resistance value, x is the number of layers of the diaphragm, a is a constant which is not zero, and b is an arbitrary constant;
(iii) calculating the membrane ion passage rate according to the formula σ ═ d/RS, wherein: sigma is the ion passing rate of the single-layer diaphragm, d is the thickness of the diaphragm, R is the resistance, and S is the area of the stainless steel wafer.
In a preferred embodiment of the present invention, the ac impedance test parameter includes an amplitude of 3 to 10mV, such as 3mV, 4mV, 5mV, 6mV, 7mV, 8mV, 9mV, and 10mV, but is not limited to the values listed, and other values not listed in the range of the values are also applicable.
The frequency is measured from 0.1Hz and lasts to 100000-200000 Hz, such as 100000Hz, 110000Hz, 120000Hz, 130000Hz, 140000Hz, 150000Hz, 160000Hz, 170000Hz, 180000Hz, 190000Hz, 200000Hz, but is not limited to the values listed, and other values not listed in the range are equally applicable.
As a preferred embodiment of the present invention, the ac impedance test of each battery is performed at least three times.
As a preferred technical solution of the present invention, at least one layer of separator is disposed in each cell.
In a second aspect, the invention provides a device for testing ionic conductivity of a diaphragm, the device is used for the method for testing ionic conductivity of a diaphragm in the first aspect, the device is a button cell, the button cell comprises a shell, the shell comprises a negative electrode shell and a positive electrode shell which are mutually buckled, a fastening base and a fastening piece are arranged in the negative electrode shell, a negative stainless steel wafer, a diaphragm clamp, a diaphragm and a positive stainless steel wafer are sequentially stacked on the surface of the fastening base, electrolyte is injected between the negative stainless steel wafer and the positive stainless steel wafer, and the negative stainless steel wafer, the diaphragm clamp, the diaphragm and the positive stainless steel wafer are fixed after the fastening base and the fastening piece are screwed in a matching manner.
It should be noted that the present invention does not specifically require and specially limit the structural features of the negative electrode case and the positive electrode case, such as size, shape, or material, and the negative electrode case and the positive electrode case in the present invention function to form the frame of the button cell, so it can be understood that other negative electrode cases and positive electrode cases that can achieve such functions can be used in the present invention, and those skilled in the art can adaptively adjust the size, shape, or material of the negative electrode case and the positive electrode case according to the use scenario and the test conditions.
As a preferable technical scheme, the button cell is assembled in an argon environment.
Preferably, the button cell is placed in a sealed environment after being assembled, and is left standing in argon for 10-15 hours, such as 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, and 15 hours, but not limited to the values listed, and other values not listed in the range of the values are also applicable.
In a preferred embodiment of the present invention, the stainless steel circular plate has a diameter of 40 to 80mm, for example, 40mm, 45mm, 50mm, 55mm, 60mm, 65mm, 70mm, 75mm, and 80mm, but the diameter is not limited to the above-mentioned values, and other values not listed in the above-mentioned range are also applicable.
Preferably, the diaphragm clamp is made of teflon.
Preferably, the thickness of the diaphragm holder is 10 to 30 μm, and may be, for example, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, 26 μm, 28 μm, 30 μm, but is not limited to the above-mentioned values, and other values not mentioned in the above-mentioned range are also applicable.
Preferably, the diaphragm clamp has an outer diameter of 40 to 60mm, for example, 40mm, 43mm, 45mm, 48mm, 50mm, 53mm, 55mm, 58mm, 60mm, but not limited to the values listed, and other values not listed in the range of the values are also applicable.
Preferably, the diaphragm clamp has an inner diameter of 20 to 30mm, for example, 20mm, 21mm, 22mm, 23mm, 24mm, 25mm, 26mm, 27mm, 28mm, 29mm, 30mm, but is not limited to the values listed, and other values not listed in the range of the values are also applicable.
As a preferred embodiment of the present invention, the electrolyte includes ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and lithium hexafluorophosphate.
Preferably, the weight ratio of the ethylene carbonate, the dimethyl carbonate and the ethyl methyl carbonate is 1: 1: 1.
preferably, the lithium hexafluorophosphate concentration is 0.5 to 2.0mol/L, for example, 0.5mol/L, 0.7mol/L, 0.8mol/L, 1.0mol/L, 1.2mol/L, 1.3mol/L, 1.5mol/L, 1.7mol/L, 1.8mol/L, 2.0mol/L, but not limited to the values listed, and other values not listed in the range of the values are also applicable.
In a preferred embodiment of the present invention, the material of the diaphragm is one or a combination of at least two of PP, PE, aramid, or non-woven fabric.
Preferably, the diameter of the separator is 10 to 20mm, for example, 10mm, 11mm, 12mm, 13mm, 14mm, 15mm, 16mm, 17mm, 18mm, 19mm, 20mm, but is not limited to the values listed, and other values not listed in the range of the values are also applicable.
Compared with the prior art, the invention has the beneficial effects that:
in the invention, the conductivity in the thickness direction of the diaphragm is tested by adopting the testing device of the diaphragm ion conductivity to evaluate the diaphragm ion passing rate, the precision is higher, the preparation is simpler, and the method can directly simulate the impedance generated by the penetration of lithium ions through the diaphragm. Meanwhile, the method does not need to use anode and cathode materials, but adopts the stainless steel wafer as the symmetrical electrode, so that the cost is saved, and the influence of other interference factors on the test is reduced.
Drawings
FIG. 1 is a schematic structural diagram of a device for testing ionic conductivity of a separator according to an embodiment of the present invention;
wherein, 1-negative electrode shell; 2-sealing ring; 3-fastening the base; 4-stainless steel wafer; 5-a diaphragm clamp; 6-a fastener; 7-positive electrode shell.
Detailed Description
It is to be understood that in the description of the present invention, the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", etc., indicate orientations or positional relationships based on those shown in the drawings, and are used only for convenience in describing the present invention and for simplicity in description, and do not indicate or imply that the device or element being referred to must have a particular orientation, be constructed and operated in a particular orientation, and thus, should not be taken as limiting the present invention. Furthermore, the terms "first", "second", etc. are used for descriptive purposes only and are not to be construed as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first," "second," etc. may explicitly or implicitly include one or more of that feature. In the description of the present invention, "a plurality" means two or more unless otherwise specified.
It should be noted that, in the description of the present invention, unless otherwise explicitly specified or limited, the terms "disposed," "connected" and "connected" are to be construed broadly, and may be, for example, fixedly connected, detachably connected, or integrally connected; can be mechanically or electrically connected; they may be connected directly or indirectly through intervening media, or they may be interconnected between two elements. The specific meaning of the above terms in the present invention can be understood by those of ordinary skill in the art through specific situations.
It should be understood by those skilled in the art that the present invention necessarily includes necessary piping, conventional valves and general pump equipment for achieving the complete process, but the above contents do not belong to the main inventive points of the present invention, and those skilled in the art can select the layout of the additional equipment based on the process flow and the equipment structure, and the present invention is not particularly limited to this.
The technical scheme of the invention is further explained by the specific implementation mode in combination with the attached drawings.
In one embodiment, the present invention provides a method for testing ionic conductivity of a separator, the method comprising: and assembling the batteries with different membrane layers, respectively carrying out alternating current impedance test on each battery, carrying out linear fitting on resistance value data obtained by testing, and calculating the ion passing rate of the membrane.
The test method comprises the following specific steps:
assembling batteries with different membrane layers, respectively carrying out alternating current impedance test on each battery, carrying out alternating current impedance test on the batteries with different membrane layers, and recording resistance value data of the batteries;
(II) drawing a Bode diagram and a Nyquist diagram according to the resistance value data of the battery, and performing linear fitting on the resistance value and the number of the corresponding diaphragm layers according to y ═ ax + b to obtain the resistance value in the thickness direction of the single-layer diaphragm, wherein: y is a resistance value, x is the number of layers of the diaphragm, a is a constant which is not zero, and b is an arbitrary constant;
(iii) calculating the membrane ion passage rate according to the formula σ ═ d/RS, wherein: sigma is the ion passing rate of the single-layer diaphragm, d is the thickness of the diaphragm, R is the resistance, and S is the area of the stainless steel wafer.
The AC impedance test parameters comprise that the amplitude is 3-10 mV, the frequency is tested from 0.1Hz and lasts to 100000-200000 Hz, and specifically, the AC impedance test of each battery is carried out at least three times. At least one separator is disposed in each cell.
In another embodiment, the invention provides a device for testing ionic conductivity of a diaphragm, as shown in fig. 1, the device is used in a method for testing ionic conductivity of a diaphragm, the device is a button cell, specifically, the button cell includes a casing, the casing includes a negative casing 1 and a positive casing 7 which are fastened to each other, a fastening base 3 and a fastening piece 6 are arranged inside the negative casing 1, a negative stainless steel disc 4, a diaphragm clamp 5, a diaphragm and a positive stainless steel disc 4 are sequentially stacked on the surface of the fastening base 3, electrolyte is injected between the negative stainless steel disc 4 and the positive stainless steel disc 4, and the fastening base 3 and the fastening piece 6 are screwed tightly to fix the negative stainless steel disc 4, the positive stainless steel disc 4, the diaphragm clamp 5 and the diaphragm.
And (3) assembling the button cell in an argon environment, further placing the button cell in a sealed environment after the button cell is assembled, and standing the button cell in the argon for 10-15 hours. The diameter of the stainless steel wafer 4 is 40-80 mm, the material of the diaphragm clamp 5 is Teflon, specifically, the thickness of the diaphragm clamp 5 is 10-30 μm, the outer diameter of the diaphragm clamp 5 is 40-60 mm, and the inner diameter of the diaphragm clamp 5 is 20-30 mm.
The electrolyte comprises ethylene carbonate, dimethyl carbonate, methyl ethyl carbonate and lithium hexafluorophosphate, and specifically, the weight ratio of the ethylene carbonate to the methyl ethyl carbonate is 1: 1: 1, and further, the concentration of lithium hexafluorophosphate is 0.5 to 2.0 mol/L. The diaphragm is made of any one or a combination of at least two of PP, PE, aramid fiber or non-woven fabrics, and specifically, the diameter of the diaphragm is 10-20 mm.
Examples1
The embodiment provides a method and a device for testing ionic conductivity of a diaphragm, and the method and the device are provided based on a specific implementation mode, wherein:
the diameter of the stainless steel wafer 4 is 40 mm;
the diaphragm clamp 5 is made of Teflon, the thickness of the diaphragm clamp 5 is 10 micrometers, the outer diameter of the diaphragm clamp 5 is 40mm, and the inner diameter of the diaphragm clamp 5 is 20 mm;
the concentration of lithium hexafluorophosphate is 0.5 mol/L;
the diameter of the diaphragm was 10 mm.
The testing device for the ionic conductivity of the diaphragm is assembled in sequence in a high-purity argon environment, then sealed and kept stand in argon for 12h, alternating current impedance testing is carried out on the testing device to obtain a resistor R0, then the diaphragm is replaced by two layers of 5-micron diaphragms, the steps are repeated to obtain R1, R2 and R3, the number of the diaphragm layers is used as abscissa data, corresponding resistors (R1, R2 and R3) are used as ordinate, and linear fitting is carried out, so that the resistance value R1 in the thickness direction of the single-layer diaphragm is measured to be 1.05 omega, the resistance value R2 is measured to be 2.36 omega, and the resistance R3 is measured to be 1.29 omega.
Examples2
The embodiment provides a method and a device for testing ionic conductivity of a diaphragm, and the method and the device are provided based on a specific implementation mode, wherein:
the diameter of the stainless steel wafer 4 is 50 mm;
the diaphragm clamp 5 is made of Teflon, the thickness of the diaphragm clamp 5 is 16 micrometers, the outer diameter of the diaphragm clamp 5 is 45mm, and the inner diameter of the diaphragm clamp 5 is 24 mm;
the concentration of lithium hexafluorophosphate is 1.0 mol/L;
the diameter of the septum was 14 mm.
The testing device for the ionic conductivity of the diaphragm is assembled in sequence in a high-purity argon environment, then sealed and kept stand in argon for 12h, alternating current impedance testing is carried out on the testing device, resistance R0 is measured, then the diaphragm is replaced into a three-layer 5-micron diaphragm, the steps are repeated to obtain R1, R2 and R3, the number of layers of the diaphragm is used as abscissa data, corresponding resistances (R1, R2 and R3) are used as ordinate, and linear fitting is carried out, so that the resistance value R1 in the thickness direction of the single-layer diaphragm is measured to be 1.35 omega, the resistance value R2 is measured to be 3.10 omega, and the resistance value R3 is measured to be 1.65 omega.
Examples3
The embodiment provides a method and a device for testing ionic conductivity of a diaphragm, and the method and the device are provided based on a specific implementation mode, wherein:
the diameter of the stainless steel wafer 4 is 60 mm;
the diaphragm clamp 5 is made of Teflon, the thickness of the diaphragm clamp 5 is 20 micrometers, the outer diameter of the diaphragm clamp 5 is 50mm, and the inner diameter of the diaphragm clamp 5 is 27 mm;
the concentration of lithium hexafluorophosphate is 1.5 mol/L;
the diameter of the septum was 18 mm.
The testing device for the ionic conductivity of the diaphragm is assembled in sequence in a high-purity argon environment, then sealed and kept stand in argon for 12h, alternating current impedance testing is carried out on the testing device, resistance R0 is measured, then the diaphragm is replaced by a four-layer 5-micron diaphragm, the steps are repeated to obtain R1, R2 and R3, the number of layers of the diaphragm is used as abscissa data, corresponding resistances (R1, R2 and R3) are used as ordinate, and linear fitting is carried out, so that the resistance value R1 in the thickness direction of the single-layer diaphragm is measured to be 1.71 omega, the resistance value R2 is measured to be 4.34 omega, and the resistance value R3 is measured to be 2.02 omega.
Examples4
The embodiment provides a method and a device for testing ionic conductivity of a diaphragm, and the method and the device are provided based on a specific implementation mode, wherein:
the diameter of the stainless steel wafer 4 is 80 mm;
the diaphragm clamp 5 is made of Teflon, the thickness of the diaphragm clamp 5 is 30 micrometers, the outer diameter of the diaphragm clamp 5 is 60mm, and the inner diameter of the diaphragm clamp 5 is 30 mm;
the concentration of lithium hexafluorophosphate is 2.0 mol/L;
the diameter of the septum was 20 mm.
The testing device for the ionic conductivity of the diaphragm is assembled in sequence in a high-purity argon environment, then sealed and kept stand in argon for 12h, alternating current impedance testing is carried out on the testing device to obtain a resistor R0, then the diaphragm is replaced by a five-layer 5-micron diaphragm, the steps are repeated to obtain R1, R2 and R3, the number of layers of the diaphragm is used as abscissa data, corresponding resistors (R1, R2 and R3) are used as ordinate, and linear fitting is carried out, so that the resistance value R1 in the thickness direction of the single-layer diaphragm is measured to be 2.04 omega, the resistance value R2 is measured to be 5.12 omega, and the resistance value R3 is measured to be 2.38 omega.
The invention provides a testing device and a testing method for diaphragm ion conductivity, which have higher accuracy and simpler preparation, and an evaluation method for diaphragm ion passing rate. The test period of developing the functional diaphragm is shortened, the test consumption is reduced, the interference of other interference factors on the ion passing rate of the diaphragm is reduced, and the test precision is improved.
The applicant declares that the above description is only a specific embodiment of the present invention, but the scope of the present invention is not limited thereto, and it should be understood by those skilled in the art that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope of the present invention are within the scope and disclosure of the present invention.
Claims (10)
1. A method for testing the ionic conductivity of a diaphragm is characterized by comprising the following steps: and assembling the batteries with different membrane layers, respectively carrying out alternating current impedance test on each battery, carrying out linear fitting on resistance value data obtained by testing, and calculating the ion passing rate of the membrane.
2. The test method according to claim 1, wherein the test method comprises the following specific steps:
assembling batteries with different membrane layers, respectively carrying out alternating current impedance test on each battery, carrying out alternating current impedance test on the batteries with different membrane layers, and recording resistance value data of the batteries;
(II) drawing a Bode diagram and a Nyquist diagram according to the resistance value data of the battery, and performing linear fitting on the resistance value and the number of the corresponding diaphragm layers according to the y ═ ax + b, thereby obtaining the resistance value in the thickness direction of the single-layer diaphragm, wherein: y is a resistance value, x is the number of layers of the diaphragm, a is a constant which is not zero, and b is an arbitrary constant;
(iii) calculating the membrane ion passage rate according to the formula σ ═ d/RS, wherein: sigma is the ion passing rate of the single-layer diaphragm, d is the thickness of the diaphragm, R is the resistance, and S is the area of the stainless steel wafer.
3. The method of claim 1, wherein the AC impedance test parameters include an amplitude of 3-10 mV and a frequency of 0.1Hz for 100000-200000 Hz.
4. The method of claim 1, wherein the ac impedance test is performed at least three times per cell.
5. The method of claim 1, wherein at least one separator is disposed in each cell.
6. The utility model provides a testing arrangement of diaphragm ionic conductivity, characterized in that, testing arrangement be used for claim 1a testing method of diaphragm ionic conductivity, testing arrangement be button cell, button cell include the casing, the casing include negative pole shell and the positive pole shell of mutual lock, negative pole shell inside be provided with fastening base and fastener, fastening base surface stack gradually and be provided with negative pole stainless steel disk, diaphragm anchor clamps, diaphragm and anodal stainless steel disk, negative pole stainless steel disk and anodal stainless steel disk between inject electrolyte, fastening base and fastener cooperation screw the back fixed negative pole stainless steel disk, diaphragm anchor clamps, diaphragm and anodal stainless steel disk.
7. The test device of claim 6, wherein the button cell is assembled in an argon environment;
preferably, the button cell is placed in a sealed environment after being assembled, and stands still for 10-15 hours in argon.
8. The testing device of claim 6, wherein the stainless steel disc has a diameter of 40-80 mm;
preferably, the diaphragm clamp is made of teflon;
preferably, the thickness of the diaphragm clamp is 10-30 μm;
preferably, the outer diameter of the diaphragm clamp is 40-60 mm;
preferably, the inner diameter of the diaphragm clamp is 20-30 mm.
9. The test device of claim 6, wherein the electrolyte comprises ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and lithium hexafluorophosphate;
preferably, the weight ratio of the ethylene carbonate, the dimethyl carbonate and the ethyl methyl carbonate is 1: 1: 1;
preferably, the concentration of the lithium hexafluorophosphate is 0.5-2.0 mol/L.
10. The testing device of claim 6, wherein the membrane is made of one or a combination of at least two of PP, PE, aramid or non-woven fabric;
preferably, the diameter of the diaphragm is 10-20 mm.
Priority Applications (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN202110703139.2A CN113433389A (en) | 2021-06-24 | 2021-06-24 | Method and device for testing ionic conductivity of diaphragm |
Applications Claiming Priority (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN202110703139.2A CN113433389A (en) | 2021-06-24 | 2021-06-24 | Method and device for testing ionic conductivity of diaphragm |
Publications (1)
| Publication Number | Publication Date |
|---|---|
| CN113433389A true CN113433389A (en) | 2021-09-24 |
Family
ID=77753871
Family Applications (1)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| CN202110703139.2A Pending CN113433389A (en) | 2021-06-24 | 2021-06-24 | Method and device for testing ionic conductivity of diaphragm |
Country Status (1)
| Country | Link |
|---|---|
| CN (1) | CN113433389A (en) |
Cited By (5)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN113945763A (en) * | 2021-11-15 | 2022-01-18 | 湖北亿纬动力有限公司 | Method for testing liquid-phase resistance of pole piece |
| CN114113839A (en) * | 2021-11-16 | 2022-03-01 | 武汉昊诚锂电科技股份有限公司 | Method for evaluating current collecting capacity of lithium-ion battery current collecting structure |
| CN114236239A (en) * | 2021-12-15 | 2022-03-25 | 湖北亿纬动力有限公司 | Testing device and testing method for diaphragm ionic conductivity |
| CN116047318A (en) * | 2022-12-26 | 2023-05-02 | 蜂巢能源科技股份有限公司 | A method and application of rapidly testing the electrical properties of a diaphragm for an ion battery |
| CN116429842A (en) * | 2023-03-20 | 2023-07-14 | 宁德时代新能源科技股份有限公司 | Electrolyte ion migration number test method, system, device and computer equipment |
Citations (7)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| JPS568535A (en) * | 1979-06-28 | 1981-01-28 | Siemens Ag | Device for measuring dissolved carbon dioxide |
| CN102185154A (en) * | 2011-04-15 | 2011-09-14 | 南京师范大学 | Nano ferric phosphate hollow sphere lithium ion battery and preparation method thereof |
| CN108281625A (en) * | 2018-01-03 | 2018-07-13 | 兰州理工大学 | A kind of nanometer of compound nucleocapsid of stannic disulfide/carbosphere and preparation method thereof |
| CN108318822A (en) * | 2017-12-18 | 2018-07-24 | 合肥国轩高科动力能源有限公司 | A method and system for measuring the conductivity of lithium battery pole pieces and separators |
| CN109360954A (en) * | 2018-09-28 | 2019-02-19 | 厦门大学 | Lithium vanadium phosphate/carbon fiber composite cathode material, preparation method and application thereof |
| CN109596995A (en) * | 2018-12-29 | 2019-04-09 | 深圳市比克动力电池有限公司 | Battery diaphragm electrical property measuring device and measuring method |
| CN111579871A (en) * | 2020-05-07 | 2020-08-25 | 深圳市星源材质科技股份有限公司 | Battery separator ionic conductivity test device and test method |
-
2021
- 2021-06-24 CN CN202110703139.2A patent/CN113433389A/en active Pending
Patent Citations (7)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| JPS568535A (en) * | 1979-06-28 | 1981-01-28 | Siemens Ag | Device for measuring dissolved carbon dioxide |
| CN102185154A (en) * | 2011-04-15 | 2011-09-14 | 南京师范大学 | Nano ferric phosphate hollow sphere lithium ion battery and preparation method thereof |
| CN108318822A (en) * | 2017-12-18 | 2018-07-24 | 合肥国轩高科动力能源有限公司 | A method and system for measuring the conductivity of lithium battery pole pieces and separators |
| CN108281625A (en) * | 2018-01-03 | 2018-07-13 | 兰州理工大学 | A kind of nanometer of compound nucleocapsid of stannic disulfide/carbosphere and preparation method thereof |
| CN109360954A (en) * | 2018-09-28 | 2019-02-19 | 厦门大学 | Lithium vanadium phosphate/carbon fiber composite cathode material, preparation method and application thereof |
| CN109596995A (en) * | 2018-12-29 | 2019-04-09 | 深圳市比克动力电池有限公司 | Battery diaphragm electrical property measuring device and measuring method |
| CN111579871A (en) * | 2020-05-07 | 2020-08-25 | 深圳市星源材质科技股份有限公司 | Battery separator ionic conductivity test device and test method |
Cited By (7)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN113945763A (en) * | 2021-11-15 | 2022-01-18 | 湖北亿纬动力有限公司 | Method for testing liquid-phase resistance of pole piece |
| CN114113839A (en) * | 2021-11-16 | 2022-03-01 | 武汉昊诚锂电科技股份有限公司 | Method for evaluating current collecting capacity of lithium-ion battery current collecting structure |
| CN114113839B (en) * | 2021-11-16 | 2024-11-08 | 武汉昊诚锂电科技股份有限公司 | A method for evaluating the current collecting capacity of a lithium-ion battery current collecting structure |
| CN114236239A (en) * | 2021-12-15 | 2022-03-25 | 湖北亿纬动力有限公司 | Testing device and testing method for diaphragm ionic conductivity |
| CN114236239B (en) * | 2021-12-15 | 2024-02-02 | 湖北亿纬动力有限公司 | A testing device for diaphragm ion conductivity and its testing method |
| CN116047318A (en) * | 2022-12-26 | 2023-05-02 | 蜂巢能源科技股份有限公司 | A method and application of rapidly testing the electrical properties of a diaphragm for an ion battery |
| CN116429842A (en) * | 2023-03-20 | 2023-07-14 | 宁德时代新能源科技股份有限公司 | Electrolyte ion migration number test method, system, device and computer equipment |
Similar Documents
| Publication | Publication Date | Title |
|---|---|---|
| US20200280051A1 (en) | Methods for making reference electrode and lithium ion battery having the same | |
| CN108318822B (en) | A method and system for measuring the conductivity of lithium battery pole pieces and separators | |
| CN106872905A (en) | A kind of full battery parameter acquisition methods of monomer lithium ion | |
| CN208460908U (en) | Three-electrode battery for measuring the electrochemically active specific surface area of a battery | |
| CN108899594B (en) | A kind of analysis method of lithium metal negative electrode expansion amplitude | |
| CN108987659A (en) | A kind of four electrode system of lithium ion soft-package battery and preparation method thereof | |
| CN107102041B (en) | Laminated three-electrode electrolytic tank for electrochemical test of in-situ lithium battery | |
| CN108508067A (en) | A method of evaluating the battery material of lithium ion battery using Symmetrical cells | |
| CN106532107A (en) | Lithium-ion button-type total battery used in experiments and manufacturing method thereof | |
| CN109581064A (en) | Measure method, apparatus, the medium of battery low temperature direct resistance | |
| CN113945763A (en) | Method for testing liquid-phase resistance of pole piece | |
| CN109974655A (en) | A kind of apparatus and method for of online no pressure detection lithium battery silicon-carbon cathode pole piece expansion | |
| CN202949008U (en) | Triple-electrode device of lithium ion battery | |
| CN206906306U (en) | A kind of electrode electrolyser of laminated type three for lithium battery test chemical in situ | |
| CN108872868A (en) | Detect integrating device, the system and method for battery pack state-of-charge and health status | |
| CN101464498B (en) | Three-electrode simulation battery equipment used for lithium ion battery | |
| CN107785625A (en) | A kind of easy electrode lithium ion battery test system of Soft Roll four | |
| CN209001049U (en) | A button-type lithium-ion symmetrical battery | |
| CN109342954A (en) | A battery testing and analysis structure and its manufacturing method and battery testing and analysis method | |
| CN211905519U (en) | Surface resistance testing equipment for vanadium battery ion exchange membrane | |
| CN114354449A (en) | Method for testing infiltration degree of winding core | |
| CN119758118A (en) | Method for testing electrochemical active area of electrode | |
| CN209640464U (en) | Battery diaphragm electrical property measuring device | |
| CN220063912U (en) | Potential detection device of pole piece | |
| CN109959823B (en) | A jig and method for measuring the impedance of the negative pole piece of a high-precision lithium ion battery with lithium insertion |
Legal Events
| Date | Code | Title | Description |
|---|---|---|---|
| PB01 | Publication | ||
| PB01 | Publication | ||
| SE01 | Entry into force of request for substantive examination | ||
| SE01 | Entry into force of request for substantive examination | ||
| RJ01 | Rejection of invention patent application after publication | ||
| RJ01 | Rejection of invention patent application after publication |
Application publication date: 20210924 |